(untitled) (Research, Society and Development, 2022)
Objective: To identify in the scientific literature the impact/contribution of educational technology in comic book format as a strategy used for health education. Method: Integrative review carried out through a search in databases (Lilacs, Medline, Bdenf, Pumed and Scielo). Held from February to November 2021. Inclusion and exclusion criteria and descriptors were established to control and obtain articles in the databases. Results: The selected sample of the research had fifteen publications. From the evaluation of the results of the selected articles, it is possible to verify the difference that the use of educational technology in comic book format represents for health promotion. Conclusion: The collected articles point out that the use of comics as a health education tool can be considered a facilitator in the communication and transmission of subjects relevant to the various areas of focus of the articles.